(3QSGdI aj efGaY GdCYVGA GdEfSGfjIs - (3GHf GdfajS , YdGA GdOjf CHh GdMSf Ydj Hf CHj GdMRe GdbQTj, GHf GdfajS,J (B687 (3g` s
(3ChdgG (B:s
(3bd GdabjQ (B: (3Ef GdebGe GdYGdi Gdehdhi CLd ef Cf jNOe HGdCTjGA GdOfjI GdOfjGhjI hgPg GdQSGdI eTJedI Ydi eYGQa heYGf McjeI aj efGaY CYVGA GdEfSGf s
(3BNQgG (B:s
(3ef Cf Cfa Gdajd jbhe dg ebGe GdjO, Ohf ZjQg ef GdMjhGfGJ Je cJGH QSGdI GdCYVGA HMeO Gddg hoMSf Jhajbg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B49 - (3U(B77s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B270 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B58s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B112 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs